Private lives of the ancient mariner : Coleridge and his children - Lefebure, Molly (Cambridge, United Kingdom : The Lutterworth Press, 2013)
A fascinating new study of Samuel Taylor Coleridge, The Private Lives of the Ancient Mariner illuminates the poet's deeply troubled personality and stormy personal life through a highly original study of his relationships. In her last published work the celebrated Coleridgean, Molly Lefebure, provides profound psychological insights into Coleridge through a meticulous study of his domestic life, drawing upon a vast and unique body of knowledge gained from a lifetime's study of the poet, and making skilful use of the letters, poems and biographies of the man himself and his family and friends.
Part one. Resurrection -- part two. Sam -- part three. Taper in a cottage window -- part four. A mystic peregrination -- part five. Trailing clouds of glory -- part six. Samuel Taylor Coleridge v. Napoleon Bonaparte -- part seven. Confrontations -- part eight. Shipwreck of the Faery Voyager.
Includes bibliographical references (pages 319-320) and index.
Print version record.
English.
JSTOR
Keywords: Coleridge, Samuel Taylor, -- 1772-1834 -- Family; Coleridge, Samuel Taylor, -- 1772-1834; Coleridge, Samuel Taylor -- 1772-1834; Poets, English -- 19th century -- Biography; Poètes anglais -- 19e siècle -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; POETRY -- English, Irish, Scottish, Welsh; Families; Poets, English; 1800-1899; Biography; Biographies; Biographies; Biographies